Proper static potential in classical lattice gauge theory at finite T - Lehmann, Alexander; Rothkopf, Alexander (Journal of high energy physics, 2021)
We compute the proper real-time interaction potential between a static quark and antiquark in classical lattice gauge theory at finite temperature. Our central result is the determination of the screened real-part of this potential, and we reconfirm the presence of an imaginary part. The real part is intimately related to the back-reaction of the static sources onto the gauge fields, incorporated via Gauss's law. Differences in the treatment of static sources in quantum and classical lattice gauge theory are discussed.
Gesehen am 09.08.2021